ON WARFARE (Annual of the Faculty of Philosophy in Skopje, 2022)
We re-examine the phenomenon of war by analysing the three main philosophies of war, by comparing the approach to the notion of war in modern security studies, by examining the main trends of warfare after 1945 and the changing nature of warfare. The author answers the questions about: Total War; the relationship between globalization and war; the new type of wars; and the so-called western way of warfare. The analysis of warfare emphasizes the changed concept of the battlefield, the political narrative of warfare, as well as the revitalization of nuclear weapons and the threat. Exploring the process of warfare cannot escape the cultural, legal and political approach of war. From a methodological point of view, the determination of accurate statistics on armed conflicts and indirect casualties, which is the most numerous categories of death, remains problematic.
Keywords: WAR; WARFARE; CLAUSEVIC; CONFLICTS; TRENDS